Food value chains configurations and resilience of rural mountain communities: three dairy business models in central Apennines (Italy) - Belliggiano, Angelo; Ievoli, Corrado; Bispini, Sara; Conti, Mauro (Frontiers in Sustainable Food Systems, 2024)
The research was held in “Alto Molise” focusing on the dairy value chain of the “caciocavallo cheese”, historically rooted in the Socio-Ecological System of the Mountain Reference Landscape. The local production system connects the environmental setting, livestock farming skills, the production of dairy goods, and socio-cultural heritage. In particular, the Focal Value Chain of caciocavallo cheese involves local natural and socio-cultural resources, it is also linked to other value chains (such as tourism and meat production), and its development can contrast the socio-environmental depletion of the territorial capital. The Value Chain is organized around the cheesemakers who hold a market power compared to others. The analysis resulted in a strong weakness of the farmers, which may threaten the very economic sustainability of the Value Chain. To represent the situation, the research identified three ideal-type of business models that outline their interaction with the Socio-Ecological System at different stages of the value chain (production, processing, retailing, and consumption) and their impact on territorial capital and the resilience of mountain rural communities, including adaptation to climate change and reverse depopulation: model A - Network variant: cheesemakers use only local raw milk establishing fair economic and social collaboration with local breeders; Model B - Market variant: cheesemakers use pasteurized milk produced in the area, in Italy or the UE for a more “industrialized” production process, model C - Autonomy variant: breeders/milk producers are also cheesemakers in this case. At the production level the environmental capital the sociocultural capital and intangible cultural heritage enter the Value Chain mainly through business models A and C. Business model B allows this connection and valorization only based on the specialization and diary enterprise reputation, connects with territorial capital of the production stage of Experiential Tourism and meat Value Chains, and the actors as processors and family businesses, but not on the territorial capital of the production stage as landscape based on the interaction of agriculture with the natural habitats. This implies a shift in the production model towards a more industrialized one with raw materials from outside the area.